Substantiation of Medical Cooling Methods in Therapy of Chronic Alcoholism - Lomakin, I. I. (Problems of Cryobiology and Cryomedicine, 2008)
On the basis of the theory of functional systems preconditions for realization of opportunities of various kinds of a medical hypothermia (a cranio-cerebral hypothermia, rhythmic cold influences, extreme aerocryotherapy) in therapy of an alcoholism are reviewed.